Islamist Exegesis of Q 3:110 - Brannon Wheeler (International Institute of Islamic Thought, 2020)
Is there an Islamic version of the UN doctrine of the "Responsibility to Protect"? Are Muslims obligated to defend their own community, and to save the rest of the world from tyranny and oppression? The UN doctrine commits member states to protect people from certain types of harm, and specifically includes protecting populations from their own governments. If a comparable Islamic doctrine exists, it is especially ironic that the UN doctrine is so frequently applied to Muslim majority countries in the Middle East. This irony allows for a new perspective on the continuing conceptual and physical conflicts between western powers and states in the Middle East.